2017
DOI: 10.1002/jsfa.8743
|View full text |Cite
|
Sign up to set email alerts
|

Sensory quality and fatty acid content of springbok (Antidorcas marsupialis) meat: influence of farm location and sex

Abstract: Farm location could influence the sensory quality and composition of springbok meat and should be considered when harvesting for meat production. Sex does not have to be considered for the marketing of springbok meat. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
(58 reference statements)
0
2
1
Order By: Relevance
“…The IMF values measured here are lower than those found in the LTL of South African sheep, goat, and grain-fed cattle (Figure 1) [39][40][41]. While the present IMF values are comparable with those found in the LTL of wild fallow deer from Hungary (2.5%) [27], they are higher than those reported for wild and farmed fallow-, red-, and roe-deer from other parts of Europe, and also exceed those found for most indigenous antelope (Figure 1).…”
Section: Proximate Compositioncontrasting
confidence: 62%
See 1 more Smart Citation
“…The IMF values measured here are lower than those found in the LTL of South African sheep, goat, and grain-fed cattle (Figure 1) [39][40][41]. While the present IMF values are comparable with those found in the LTL of wild fallow deer from Hungary (2.5%) [27], they are higher than those reported for wild and farmed fallow-, red-, and roe-deer from other parts of Europe, and also exceed those found for most indigenous antelope (Figure 1).…”
Section: Proximate Compositioncontrasting
confidence: 62%
“…Values obtained in the present study appear in the first column (label marked in bold). The superscript numbers indicated after each species refer to references in the reference list[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. * Indicates studies in which a significant sex effect was found; "R" indicates studies in which a range of values were reported.…”
mentioning
confidence: 99%
“…The 963 nm band is related to the third overtone stretching of an O-H bond (Barbin et al, 2012) associated with the moisture content, and the 1143 nm band corresponds to the second overtone C-H stretching bonds representing the intramuscular fat (Cozzolino & Murray, 2004). Numerous researchers conducting studies on proximate chemical composition of game meat have revealed that the male animals have lower fat and higher moisture contents than females (Von la Chevallerie, 1972;Neethling, Britz, & Hoffman, 2014a;Neethling, Muller, van der Rijst, & Hoffman, 2018). Therefore, the difference in intramuscular fat and moisture content of impala meat compared to the other species might have been caused by the fact that only male impala animals were slaughtered in this study (Table 1).…”
Section: Tablementioning
confidence: 99%